Tomato Endophytic Bacteria Composition and Mechanism of Suppressiveness of Wilt Disease (Fusarium oxysporum) - Zhang, Zeyu; Li, Ji; Zhang, Zengqiang; Liu, Youzhou; Wei, Yuquan (Frontiers in Microbiology, 2021)
Tomato wilt disease, caused by the Fusarium oxysporum is an ever-increasing threat for agricultural production, and unreasonable fertilization and pesticide abuse caused environmental challenge. Increasing evidence suggested that microbiomes or those associated with crops, played key roles on plant health. Plant disease dynamics were affected by multiple biotic and abiotic factors including phytopathogen population density, the genetic type of the pathogen and the host, in particular, the composition and assembly of the host-associated microbiome. However, it was unclear how pathogen invasion interaction and correlate with endophytic bacterial communities in natural field conditions. To study this, we sampled temporally the tomato plants that were exposed to Fusarium oxysporum invasions over one crop season. High-throughput sequencing were performed to explore the correlation between agricultural practice, pathogen invasion, and endophytic microbiota communities. Results showed that pathogen invasion had clear effect on the endophytic and a strong link between increased pathogen densities and reduced abundance of Bacillus.sp, which are crucial taxonomy for suppressiveness to Fusarium oxysporum in vitro and in greenhouse condition. In summary, monitoring the dynamics of endophytic bacteria communities and densities of pathogen could thus open new avenue for more accurate disease diagnostics and high-efficiency screening antagonisms methods in the future, and our results will broaden the agricultural view of beneficial microbiota as biological control agents against plant pathogen.